SPESIES BURUNG (FAMILI MUSCICAPIDAE) DI KAWASAN WISATA BURNI TELONG KABUPATEN BENER MERIAH - Ahadi, Rizky; Kamaliah, Kamaliah; Supranto, Endi (KENANGA : Journal of Biological Sciences and Applied Biology, 2025)
Birds play an important role as an ecosystem balancer through the process of seed dispersal, pollination, and pest control, thus helping to maintain the integrity of biological resources. This study aims to identify bird species from the Muscicapidae family and analyze their diversity in the Burni Telong Tourism Area, Bener Meriah Regency. The method used is point count with 10 observation points. Each point is observed for 20 minutes within a radius of 50 meters, with a distance between points of 200 meters. Species identification was carried out using a guidebook, the population was calculated quantitatively, and its conservation status was identified. The results showed that there were 33 individuals of brushbirds from the Muscicapidae family consisting of four species, namely the Mangrove blue flycatcher (Cyornis rufigastra), Little pied flycatcher (Ficedula westermanni), Grey headed canary flycatcher (Culicicapa ceylonensis), and the Matinan flycatcher (Cyornis sanfordi). These findings indicate that the Muscicapidae population in this area is still well maintained. Of the four species of flycatchers, only the Matinan flycatcher (Cyornis sanfordi) is included in the protected category based on conservation status. Keywords : Aves Species, Muscicapidae Family, Burni Telong Tourism.